2011
DOI: 10.2495/eres110241
|View full text |Cite
|
Sign up to set email alerts
|

The effects of multiple vertical baffles on sloshing phenomenon in rectangular tanks

Abstract: One of the phenomena in storage tanks subjected to earthquake excitations is the sloshing of impounded liquid. The use of baffles for reducing the sloshing effects has been taken into consideration by some researchers in recent years, however, the use of multiple baffles has not been taken into consideration so much. In this study the effect of using multiple vertical baffles in rectangular tanks has been investigated numerically by Finite Element Analyses. After verification of the numerical modeling, tanks w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Many academicians have been investigating the sloshing effects using baffles, however the usage of several baffles has not gained much popularity. Hosseini and Farshadmanesh examined the impact of several vertical barriers on sloshing in rectangular tanks using the finite element method [16]. They observed that two or three vertical baffles could minimize the sloshing impact to a great extent.…”
Section: Introductionmentioning
confidence: 99%
“…Many academicians have been investigating the sloshing effects using baffles, however the usage of several baffles has not gained much popularity. Hosseini and Farshadmanesh examined the impact of several vertical barriers on sloshing in rectangular tanks using the finite element method [16]. They observed that two or three vertical baffles could minimize the sloshing impact to a great extent.…”
Section: Introductionmentioning
confidence: 99%